Determinants of Anemia among Pregnant Women at Public Hospitals in West Shewa, Central Ethiopia: A Case-Control Study - Berhanu Senbeta Deriba; Elias Teferi Bala; Gizachew Abdissa Bulto; Tinsae Abeya Geleta; Agumas Fentahun Ayalew; Addis Adera Gebru; Habtamu Oljira Desta; Mengistu Benayew Shiferaew; Lidya Zerihun Sahile (Anemia)
Introduction. Anemia is highly dominant among pregnant women due to the need for iron for women themselves and their fetuses. Nearly half a billion globally and around one-third in Ethiopia of pregnant women were affected by anemia which has both health and economic impact. Therefore, this study aimed to identify the determinants of anemia among pregnant women attending antenatal care at public hospitals in the West Shewa zone, Oromia regional state, Central Ethiopia, 2019. Methods. An unmatched case-control study was conducted at public hospitals in the West Shewa zone, Ethiopia, from February to April 2019. A consecutive sampling was used to select study participants. Data were collected by a structured questionnaire, and the collected data were entered into Epi Info version 7 and SPSS version 23 for analyses. Descriptive statistics such as tables, graphs, and proportions were used to present the data. Binary and multiple logistic regression analyses were computed to identify the determinants of anemia. Adjusted odds ratio (AOR) with 95% confidence interval (CI) and p value <0.05 were used to determine the presence of an association. Result. A total of 426 women (142 cases and 284 controls) participated in this study with a 95.3% response rate. Family size >5 (AOR = 2.95, 95% CI: 1.34–6.50), peptic ulcer diseases (PUD) (AOR = 2.85, 95% CI: 1.14–7.13), having the previous history of abortion (AOR = 2.84, 95% CI: 1.08–7.47), birth interval <2 years (AOR = 2.61, 95% CI: 1.20–5.70), antepartum hemorrhage (APH) (AOR = 6.05, 95% CI: 1.95–18.81), and not using latrine (AOR = 3.45, 95% CI: 1.30–9.24) were the identified determinants of anemia. Conclusions. Family size, PUD, abortion, birth interval, APH, and unable to use latrine were the determinants of anemia among pregnant women. Therefore, the intervention on anemia prevention should consider the promotion of family planning methods and counseling on latrine utilization.